Question and Answers Forum

All Questions      Topic List

Differentiation Questions

Previous in All Question      Next in All Question      

Previous in Differentiation      Next in Differentiation      

Question Number 38232 by rahul 19 last updated on 23/Jun/18

Differentiate   tan^(−1) ((((√(1+x^2 ))−1)/x))    without using any trigonometric   substitution !

Differentiatetan1(1+x21x)withoutusinganytrigonometricsubstitution!

Commented by math khazana by abdo last updated on 23/Jun/18

we have f(x)=arctan(u(x))with   u(x)=(((√(1+x^2 )) −1)/x) = ((1+x^2 −1)/(x((√(1+x^2 )) +1))) = (x/((√(1+x^2 ))+1))  (x≠0) ⇒f^′ (x)= ((u^′ (x))/(1+(u(x))^2 )) but  u^′ (x)= (((√(1+x^2 ))+1 −x((x/(√(1+x^2 )))))/(((√(1+x^2 ))+1)^2 ))  =((1+x^2  +(√(1+x^2 )) −x^2 )/((√(1+x^2 ))((√(1+x^2 ))+1)^2 )) = ((1+(√(1+x^2 )))/((√(1+x^2 ))((√(1+x^2 ))+1)^2 )) ⇒  f^′ (x) = ((1+(√(1+x^2 )))/((√(1+x^2 ))((√(1+x^2 ))+1)^2 )) .  (1/(1+((x/(√(1+x^2 ))) +1)^2 ))  =((1 +(√(1+x^2 )))/(√(1+x^2 ((√(1+x^2 ))+1)^2 )))    ((1+x^2 )/(1+x^2 +(x+(√(1+x^2 )))^2 ))  = (((√(1+x^2 )) +1+x^2 )/(((√(1+x^2  )) +1)^2 ( 1+x^2  +(x+(√(1+x^2 )))^2 )) .

wehavef(x)=arctan(u(x))withu(x)=1+x21x=1+x21x(1+x2+1)=x1+x2+1(x0)f(x)=u(x)1+(u(x))2butu(x)=1+x2+1x(x1+x2)(1+x2+1)2=1+x2+1+x2x21+x2(1+x2+1)2=1+1+x21+x2(1+x2+1)2f(x)=1+1+x21+x2(1+x2+1)2.11+(x1+x2+1)2=1+1+x21+x2(1+x2+1)21+x21+x2+(x+1+x2)2=1+x2+1+x2(1+x2+1)2(1+x2+(x+1+x2)2.

Answered by tanmay.chaudhury50@gmail.com last updated on 23/Jun/18

let find the answer using trigo...  then without trigo...  y=tan^(−1) ((((√(1+x^2 )) −1)/x))  x=tank   (dx/dk)=sec^2 k=1+x^2   y=tan^(−1) (((seck−1)/(tank)))  y=tan^− (((1−cosk)/(sink)))  y=tan^(−1) (tan(k/2))  y=(k/2)   (dy/dk)=(1/2)  (dy/dx)=(dy/dk)×(dk/dx)=(1/2)×(1/(1+x^2 ))

letfindtheanswerusingtrigo...thenwithouttrigo...y=tan1(1+x21x)x=tankdxdk=sec2k=1+x2y=tan1(seck1tank)y=tan(1cosksink)y=tan1(tank2)y=k2dydk=12dydx=dydk×dkdx=12×11+x2

Answered by MJS last updated on 23/Jun/18

(d/dx)[arctan x]=(1/(x^2 +1))  this is a standard derivate...  we get it this way:  arctan x=f(x)  x=tan(f(x))  (d/dx)[x]=(d/dx)[tan(f(x))]  1=sec^2 (f(x))f′(x)  1=sec^2 (arctan x)f′(x)  f′(x)=(1/(sec^2 (arctan x)))  sec^2  α=(1/(cos^2  α))=((sin^2  α +cos^2  α)/(cos^2  α))=tan^2  α +1  f′(x)=(1/(tan^2 (arctan x)+1))=(1/(x^2 +1))    (d/dx)[arctan (((√(1+x^2 ))−1)/x)]=  =(((d/dx)[(((√(1+x^2 ))−1)/x)])/(((((√(1+x^2 ))−1)/x))^2 +1))=((((√(1+x^2 ))−1)/(x^2 (√(1+x^2 ))))/(2((1+x^2 −(√(1+x^2 )))/x^2 )))=  =(1/(2(1+x^2 )))

ddx[arctanx]=1x2+1thisisastandardderivate...wegetitthisway:arctanx=f(x)x=tan(f(x))ddx[x]=ddx[tan(f(x))]1=sec2(f(x))f(x)1=sec2(arctanx)f(x)f(x)=1sec2(arctanx)sec2α=1cos2α=sin2α+cos2αcos2α=tan2α+1f(x)=1tan2(arctanx)+1=1x2+1ddx[arctan1+x21x]==ddx[1+x21x](1+x21x)2+1=1+x21x21+x221+x21+x2x2==12(1+x2)

Answered by ajfour last updated on 23/Jun/18

let x=tan θ  y=tan^(−1) (((1−cos θ)/(sin θ)))    =tan^(−1) (tan (θ/2)) = (θ/2)  y=(1/2)tan^(−1) x  (dy/dx) = (1/(2(1+x^2 ))) .

letx=tanθy=tan1(1cosθsinθ)=tan1(tanθ2)=θ2y=12tan1xdydx=12(1+x2).

Answered by tanmay.chaudhury50@gmail.com last updated on 23/Jun/18

tany=(((√(1+x^2 )) −1)/x)  xtany+1=(√(1+x^2  ))  x^2 tan^2 y+2xtany+1=1+x^2   x^2 tan^2 y+2xtany−x^2 =0  x^2 (tan^2 y−1)+2xtany=0  x{x(tan^2 y−1)+2tany}=0  x(tan^2 y−1)+2tany=0  x=((2tany)/(1−tan^2 y))=((2sinycosy)/(cos^2 y−sin^2 y))=tan2y  (dx/dy)=2sec^2 2y^ =2(1+x^2 )  (dy/dx)=(1/(2(1+x^2 )))

tany=1+x21xxtany+1=1+x2x2tan2y+2xtany+1=1+x2x2tan2y+2xtanyx2=0x2(tan2y1)+2xtany=0x{x(tan2y1)+2tany}=0x(tan2y1)+2tany=0x=2tany1tan2y=2sinycosycos2ysin2y=tan2ydxdy=2sec22y=2(1+x2)dydx=12(1+x2)

Terms of Service

Privacy Policy

Contact: info@tinkutara.com